Pharmacokinetic and metabolomic analyses of Mangiferin calcium salt in rat models of type 2 diabetes and non-alcoholic fatty liver disease - He Lin (BMC Pharmacology and Toxicology, 2020)
Abstract Background Non-alcoholic fatty liver is one of the most common comorbidities of diabetes. It can cause disturbance of glucose and lipid metabolism in the body, gradually develop into liver fibrosis, and even cause liver cirrhosis. Mangiferin has a variety of pharmacological activities, especially for the improvement of glycolipid metabolism and liver injury. However, its poor oral absorption and low bioavailability limit its further clinical development and application. The modification of mangiferin derivatives is the current research hotspot to solve this problem. Methods The plasma pharmacokinetic of mangiferin calcium salt (MCS) and mangiferin were monitored by HPLC. The urine metabolomics of MCS were conducted by UPLC-Q-TOF-MS. Results The pharmacokinetic parameters of MCS have been varied, and the oral absorption effect of MCS was better than mangiferin. Also MCS had a good therapeutic effect on type 2 diabetes and NAFLD rats by regulating glucose and lipid metabolism. Sixteen potential biomarkers had been identified based on metabolomics which were related to the corresponding pathways including Pantothenate and CoA biosynthesis, fatty acid biosynthesis, citric acid cycle, arginine biosynthesis, tryptophan metabolism, etc. Conclusions The present study validated the favorable pharmacokinetic profiles of MCS and the biochemical mechanisms of MCS in treating type 2 diabetes and NAFLD.